Improving Learning Outcomes through Make A Match Method Learning in Social Studies - Tetep Tetep; Melani Shofaria; Ade Suherman (Institut Pendidikan Indonesia, 2022)
Social studies learning tends to be a subject that is less attractive to students. This can be caused by the learning model that is not appropriate and the presentation is still monotonous, so that students become bored and lack enthusiasm in learning. It is known that the results of the Social Studies test for class VII, 23 out of 32 students scored <70, which means that student learning outcomes are low. This study aims to determine the implementation of the make a match type of cooperative learning model in improving student learning outcomes in social studies subjects. This study uses a quantitative approach with a quasi-experimental method (quasi-experimental). Sources of data were taken from students of class VII MTs. Exactly Tarogong Garut, totaling 42 students. Data collection techniques were carried out using tests and observation sheets. Based on the results of the study, it can be concluded: 1) The implementation of the make a match cooperative model in improving student learning outcomes in social studies subjects is included in good criteria. 2) Social studies learning with the make a match cooperative learning model is effective in improving student learning outcomes. It can be seen in the N-Gain results that the experimental class got 0.36 results in the